Anxiety Disorder Through the Quranic Paradigm - Azizah, Elima Amiroh Nur; Mukholifah, Siti; Ulinnuha, Hanna; Andriawan, Didik; Surur, Aziz Miftahus (IAIN Ponorogo, 2024)
This article aims to provide an insightful examination of strategies for addressing anxiety disorder based on interpretations of the Qur’an. In Indonesia, the prevalence of anxiety is alarmingly high, with 9,162,886 reported cases of depression in the past two years alone. Given the Qur’an’s revered status as a guidance book, exploring its teachings on anxiety is essential to address this pressing issue. Employing a qualitative research approach focused on a literature review, this study draws from various sources, including scholarly books and articles. The research outcomes highlight several theoretical frameworks derived from the Qur’an for tackling anxiety, such as (1) mindfulness—a meditative therapy aimed at clearing the mind of negative experiences and redirecting focus toward positivity; (2) cognitive therapy—recalibrating one’s mindset toward optimistic perspectives, and (3) fostering resilient attitudes by steadfastly confronting adversities.Keyword: Anxiety Disorder; al-Qur’an; Exegesis